2018
DOI: 10.1007/s00426-018-1078-4
|View full text |Cite
|
Sign up to set email alerts
|

Is the head-fake effect in basketball robust against practice? Analyses of trial-by-trial adaptations, frequency distributions, and mixture effects to evaluate effects of practice

Abstract: Reactions to the pass of a basketball player performing a head fake are typically slower than reactions to a basketball player who passes without a head fake (i.e., head-fake effect). The present study shows that extensive practice reduces the head-fake effect in basketball. Additional analyses were conducted to explore the mechanism behind the reduced head-fake effect. First, we analyzed whether or not participants developed some control over the processing of irrelevant gaze direction, as indicated by specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…In other areas dealing with inhibition of information or responses, an effort has been made to transfer fundamental research principles to applied settings. For example, it was shown that the conflict resolution process as measured by classical cognitive psychological tasks such as the Stroop task or Eriksen flanker task [ 71 , 72 ] is conceptually similar and abides by the same rules as deceptive actions in sports [ 73 - 75 ]. Interestingly, recent studies provide evidence that even the underlying neural generators of these 2 conceptually analog tasks are similar [ 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other areas dealing with inhibition of information or responses, an effort has been made to transfer fundamental research principles to applied settings. For example, it was shown that the conflict resolution process as measured by classical cognitive psychological tasks such as the Stroop task or Eriksen flanker task [ 71 , 72 ] is conceptually similar and abides by the same rules as deceptive actions in sports [ 73 - 75 ]. Interestingly, recent studies provide evidence that even the underlying neural generators of these 2 conceptually analog tasks are similar [ 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other areas dealing with inhibition of information or responses, an effort has been made to transfer fundamental research principles to applied settings. For example, it was shown that the conflict resolution process as measured by classical cognitive psychological tasks such as the Stroop task or Eriksen flanker task [71,72] is conceptually similar and abides by the same rules as deceptive actions in sports [73][74][75]. Interestingly, recent studies provide evidence that even the underlying neural generators of these 2 conceptually analog tasks are similar [76,77].…”
Section: The Stop-signal Taskmentioning
confidence: 99%
“…Thereby, the aim of a basketball player is to deceive the opponent about the throwing direction, so that the pass to a team member can be completed successfully. Several studies showed that participants react slower and more error-prone to the direction of a pass with a head fake compared to a pass without a head fake, signifying the so-called head-fake effect [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our earlier studies [e.g., 4 , 6 ], we now refer to head orientation instead of gaze direction as task-irrelevant, interfering stimulus feature. The head-fake effect in basketball has proven to be very robust and can even be observed after extensive practice [ 5 ], and in high-level basketball experts [ 8 ]. Moreover, the head-fake effect has been found with static as well as dynamic images and with simple (i.e., keypress) as well as complex (i.e., whole body movement) responses [ 9 ].…”
Section: Introductionmentioning
confidence: 99%